„Zbrodnia i kara” Fiodora Dostojewskiego w ujęciu doktryny eurazjatyckiej Aleksandra Dugina - Bala, Maciej (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The present article amounts to an attempt to analyze the work Axe is the name of mine by Alexander Dugin — a theorist of Eurasianism ideology in Russia. In this article Dugin touches upon the novel Crime and Punishment by Fyodor Dostoyevsky. Dugin analyzes the novel in the context of cultural opposition between the orthodox Russia and the secular Western Europe, whose symbol is the capital of the Russian Empire— Saint Petersburg. The city in this case is the negation of the orthodox tradition of Moscow — The Third Rome. Dugin extremely relativized the meaning of Dostoyevsky‘snovel.